Modelling the intradermal delivery of microneedle array patches for long-acting antiretrovirals using PBPK - Rajoli, Rajith KR (Eur J Pharm Biopharm, 2019)
INTRODUCTION: Existing HIV therapy using oral antiretrovirals (ARVs) can result in pill fatigue and sub-optimal adherence. Microneedle array patches (MAPs) offer non-invasive, blood-free and painless drug delivery, and may improve patient adherence. The objective of this study was to develop a novel physiologically-based pharmacokinetic (PBPK) model to simulate the systemic pharmacokinetics of cabotegravir and rilpivirine MAPs using the intradermal route. METHODS: The developed PBPK models were qualified against observed pharmacokinetic data after intramuscular (IM) and intradermal administration of long-acting nanoformulated rilpivirine to rats, and for IM administration of both drugs to healthy adults. Qualified models were then utilised to estimate suitable MAP characteristics (e.g. nanoformulation dose and release rates) and inform dosing strategies to maintain plasma concentrations above target trough concentrations for the designated dosing interval. RESULTS: PBPK models simulated q4-weekly loading and maintenance doses of 360 mg and 180 mg for long-acting formulated cabotegravir between the release rates of 1×10(−3) – 3×10(−3) h(−1) and 1×10(−3) – 1.5×10(−3) h(−1) respectively, for a 70 kg adult. Estimated patch size was 60 cm(2) for a 360 mg dose of cabotegravir. For q4-weekly dosing, rilpivirine required a 1080 mg loading dose and a 540 mg maintenance dose with release rates of 1.5×10(−3) – 2.5×10(−3) h(−1) and 5×10(−4) – 1×10(−3) h(−1), respectively. Weekly dosing was also evaluated to assess the potential application from a smaller patch size. The ability to self-administer via a patch that is only left in place for a short duration makes longer durations less important than for some other long-acting approaches. Weekly cabotegravir required 60 mg between release rates 7×10(−3) – 9×10(−3) h(−1) and rilpivirine required 270 mg and 180 mg respectively between release rates of 7×10(−3) – 9×10(−3) h(−1). DISCUSSION: This model estimated optimal dose and release rates for cabotegravir and rilpivirine MAPs. Our approach provides a computational platform to support rational development of intradermal administration strategies to tackle problems associated with chronic oral ARV administration.